Chemically diverse polyacrylate and polyacrylamide surfaces for human cardiomyocyte culture and their effect on phenotype - Patel, Asha K. (2014)
Human pluripotent stem cell (hPSC) derived cardiomyocytes can provide robust in vitro models for pharmaceutical drug screening and modelling cardiac disease. To fully realise these potentials, hPSC-cardiomyocytes must be reproducibly cultured to a more mature state than has thus far been achieved. Defined and well controlled culture conditions underpin the ability to derive hPSC-cardiomyocytes of consistent quality. These include cell source, culture medium and substrate. This thesis is concerned with the latter; culture substrates are currently biological in nature creating inherent variability in culture conditions. There is limited knowledge on the interaction between cardiomyocytes and synthetic, non-biological substrates making rational design of materials impractical. To aid discovery of novel culture substrates, 115 polyacrylate and polyacrylamide substrates were microarrayed and investigated using a parallel screening approach. The use of polyacrylates and polyacrylamides as biomaterials has been demonstrated previously, including contact lenses, bone cements and hydrogels to support cells. The diverse chemistry exhibited across the range of polymers enables modelling of structure-activity relationships between substrate chemistry and cardiomyocyte behaviour. Cardiomyocytes derived from human embryonic stem cells (hESC) were cultured on the microarrays in the presence and absence of serum. Attachment density (nuclei count via DAPI staining) and cardiomyocyte spread (surface area using sarcomeric α-actinin immunostaining) on each substrate was acquired by automated fluorescence microscopy and image analysis software.